Pengaruh Peran Tiga Tungku (Tokoh Pemerintah, Tokoh Adat dan Tokoh Agama) dalam Gaya Kepemimpinan terhadap Kinerja Aparat Kampung di Kota Jayapura - Musa Yan Jouwe; Eka Afnan Troena; Surachman -; Margono Setiawan (Jurnal Aplikasi Manajemen, 2011)
The objectives of this research is to (1) Determine the influence of government figures, traditional figures and religious figures on the performance of village officials; 2) Determine the influence of government figures, traditional figures and religious figures of the leadership style of the village authorities; 3) Determine the influence of leadership style on the performance of village officials; 4) Knowing the influence of government leaders, traditional leaders and religious figures on the performance of village officials through a leadership style.Respondents of this research is the leadership component in the village in Jayapura, amounting to 172 people. The research location is in Jayapura. Data analysis method used was path analysis.The result of this research: 1) Traditional figures and religious figures influence significantly toward leadership styles; 2) government figures has influence less significant toward leadership styles; 3) Government figure and traditional figures influence significantly toward performance of village officers; 4) Religious figures has influence less significant toward performance of village officers; 5) leadership style significantly toward performance of village officers.Keywords: Leadership role, Leadership style, Performance of village officers